Nursing students' perceptions of patient dignity. (February 2016) - Papastavrou, Evridiki; Efstathiou, Georgios; Andreou, Christos
Background: Respecting patients' dignity has been described as a fundamental part of nursing care. Many studies have focused on exploring the concept of patients' dignity from the patient and nurse perspective, but knowledge is limited regarding students' nursing perceptions and experiences. Objective: To explore the issue of patients' dignity from the perspective of nursing students. Research design: A qualitative study was employed with the formation of four focus groups and the participation of nursing students. Data were analysed via a thematic content analysis of the discussions. Participants and research context: Thirty-four nursing students of a Cyprus University participated in the four focus groups. Each group was homogenous in terms of the year of study and heterogeneous in terms of clinical practice in various wards. Ethical consideration: The study's protocol was reviewed and approved by the Cyprus National Bioethics Committee. Ethical standards were followed throughout the study. Findings: Several factors that maintain or compromise patients' dignity emerged. These factors were grouped into five themes: (a) patients' preferences, verbal abuse and regarding a patient as a unique person; (b) privacy and confidentiality; (c) loss of autonomy and need for help; (d) discrimination and (e) attribution and reciprocity. Discussion: Different understandings of the perceived concept of dignity and the factors that maintain or compromise patient's dignity were expressed through the eyes and the feelings of nursing students. Students highlighted the importance of promoting patient dignity as an important component of nursing care. Conclusion: Nurse educators can use the findings of this study in order to tailor nursing programmes to emphasise the importance of respecting patients' dignity. In addition, nurse ward managers can use the findings as means for persuading nurses to change current behaviour.